Clinical outcomes of different 17β-estradiol drug regimens and their impact on endometrial receptivity - Luo, Beining; Zhu, Xuehong; Tang, Ni; Lin, Zhong; Yao, Jun; Chen, Zhengqin; Liang, Zhuo; Wu, JinXiang; Huang, Bingsheng; Huang, Pinxiu (Frontiers in Endocrinology, 2025)
BackgroundClinically, it has been observed that vaginal administration of the same dose of Micronized 17-beta estradiol hemihydrate (the Estradiol tablets of Femoston) significantly increases serum estradiol levels compared to oral administration. However, the clinical outcomes associated with this route of administration remain unclear. Additionally, the concentration of estradiol in endometrial tissue following vaginal administration of Micronized 17-beta estradiol hemihydrate (M17EH), as well as its potential impact on endometrial receptivity, has been poorly investigated.ObjectiveTo explore the relationship between different drug regimens of M17EH hormone replacement (HRT) and serum estradiol level, endometrial thickness and embryo implantation outcome in patients with thin endometrium during the frozen-thawed embryo transfer (FET) cycle, and to analyze the estradiol concentration in endometrial tissue of oral and vaginal administration of M17EH and its influence on endometrial receptivity.MethodA retrospective analysis was conducted on patients with thin endometrium. Subjects were divided into three groups based on different estrogen formulations and administration routes: Group A [oral Estradiol Valerate Tablets (Progynova)], Group B (oral M17EH), and Group C (oral combined with vaginal M17EH). Endometrial thickness, and clinical outcomes were compared across the three groups. For Groups B and C, endometrial tissue samples were collected five days after progesterone conversion. Estradiol concentration in tissues was detected and the endometrial receptivity markers [leukemia inhibitory factor, (LIF) and Mucins, (Muc1)] were evaluated.ResultsSerum estradiol levels and endometrial thickness in Group C were significantly higher than those in the other two groups (P < 0.05). While there were no statistically significant differences in abortion rate, and live birth rate among the three groups, the live birth rate was highest in Group C. Estradiol concentration in the endometrium was significantly higher following vaginal administration of M17EH compared to oral administration (P<0.05). No significant differences were observed in the expression of endometrial receptivity markers (LIF and MUC1) between oral and vaginal administration groups.ConclusionIn FET cycles, a HRT regimen combining oral and vaginal administration of Micronized 17-beta estradiol hemihydrate is more conducive to endometrial growth. Although vaginal administration results in higher estrogen levels, it does not appear to compromise endometrial receptivity.